Polish Marxism after Luxemburg - Toporowski, Jan (Research in political economy ;, 2022)
In this 37th issue of the Research in Political Economy series, Jan Toporowski and leading experts offer a unique and insightful overview of Polish Marxism after Luxemburg, serving as an introduction to some key themes and the ideas of several Polish political economists. Polish Marxism after Luxemburg covers various ideas that emerged around the same period as Rosa Luxemburg was active, such as Ludwik Krzywicki who pioneered the study of monopoly finance capital and suggested the possibility of industrial feudalism. Chapters illustrate the current relevance of these thinkers and highlight the development from Polish Marxism of Michal Kalecki and Oskar Lange, who went on to become one of the founders of what came to be called the Keynesian Revolution in macroeconomics and economic policy. After exploring the relationship of Kalecki to Marxism, through the work of Luxemburg. Polish Marxism after Luxemburg also illuminates a selection of Polish discussions in the political economy from the second half of the twentieth century, particularly in the circle of political economists around Oskar Lange, like Wlodzimierz Brus and Tadeusz Kowalik.